# FOIL Method

How to use the FOIL method to multiply two binomials (a + b)(c + d): formula, 1 example, and its solution.

## Formula

The FOIL method is a way

to multiply two binomials:

(a + b)(c + d).

FOIL is the order of multiplication.

Multiply the First two terms: ac.

Multiply the Outer terms: +ad.

Multiply the Inner terms: +bc.

Multiply the Last two terms: +bd.

So (a + b)(c + d) = ac + bd + bc + bd.

## Example(x - 2)(x - 3)

Solution

Solution (Detail)

First multiply the First two terms.

x⋅x = x^{2}

Multiply the Outer terms.

x⋅(-3) = -3x

Multiply the Inner terms.

(-2)⋅x = -2x

And multiply the Last two terms.

(-2)⋅(-3) = +6

So (x - 2)(x - 3) = x^{2} - 3x - 2x + 6.

-3x - 2x = -5x

So

x^{2} - 5x + 6

is the answer.